Mesenchymal Stem Cell-Derived Extracellular Vesicles: Immunomodulatory Effects and Potential Applications in Intervertebral Disc Degeneration. (18th February 2022) - Hu, Shaojun; Xing, Hongyuan; Zhang, Jiangnan; Zhu, Zemin; Yin, Ying; Zhang, Ning; Qi, Yiying
Abstract : Intervertebral disc (IVD) degenerative disease is a common health problem worldwide. Administration of mesenchymal stem cells (MSCs) in intervertebral disc degeneration (IVDD) has been widely explored in recent years. However, transplantation of MSCs is restricted by several factors. Currently, paracrine signaling is one of the main mechanisms by which MSCs play a therapeutic role in disc regeneration. Extracellular vehicles (EVs) are the main paracrine products of MSCs. They show great potential as an effective alternative to MSCs and play immunomodulation roles such as anti-inflammatory effects, antioxidative stress, antiapoptosis, and antiextracellular matrix (ECM) degradation during treatment of IVDD. This review focuses on the immunomodulatory effect of MSC EVs and their potential applications.